Correlation of serum sHLA‐G levels with cyst stage in patients with cystic echinococcosis: is it an immune evasion strategy?. (20th June 2016) - Mariconti, M.; Meroni, V.; Badulli, C.; Brunetti, E.; Tinelli, C.; De Silvestri, A.; Tamarozzi, F.; Genco, F.; Casulli, A.; Martinetti, M.
Summary: Patients with cystic echinococcosis (CE) can harbour cysts for years or even decades, apparently without effect of the immune system on the metacestode. Although several immune evasion mechanisms by echinococcal cysts have been described, it is unclear whether the human leucocyte antigen (HLA) system plays a role in the susceptibility or resistance to CE in humans. HLA‐G molecules are known to exert a suppressive action on dendritic cells maturation and on natural killer (NK) cells functions, therefore hampering T‐cell responses and NK cytolysis. HLA‐G plays an important role in immune tolerance, is involved in foetus and in allotransplant tolerance, and may be involved in tumoral and viral immune evasion. In this study, we assessed the presence and levels of soluble HLA‐G (sHLA‐G) in patients with CE using a commercial ELISA kit to determine whether host's HLA‐G may have a role in the course of human CE.